دراسة تحليلية لمعاييؤ التدقيق الجزائؤية الحديثة - صفاء, بكوشه; أمال, موساوي; نبيلة, موساوي (جامعة الوادي - University of Eloued, 2023)
"الملخص: تمثل ىذه الدراسة دراسة تحليلو لدعايير التدقيق الجزائرية الحديثة )دراسة تحليلية لدى الخبراء المحاسبين ومحافظي الحسابات( كما تهدف ىذه الدراسة إلى معرفة مدى تطبيق محافظي الحسابات وخبراء محاسبين لدعايير للتدقيق الجزائرية بصفة في الجزائر أجريت الدراسة بالاعتماد على أسلوبين الأول وثائقي )وصفي( بالاطلاع على عدد من الأدبيات لتوضيح الخلفية النظرية لدراسة تحليلو لدعايير التدقيق الجزائرية الحديثة )دراسة تحليلية لدى الخبراء المحاسبين ومحافظي الحسابات(، أما الأسلوب الثاني مسحي )تحليلي( عن طريق دراسة استكشافية من خلال الاستبيان كأداة لجمع البيانات، إذ تم قياس معامل الصدق حيث أنو تم التوصل إلى درجة عالية من الثبات لعينة مكونة من وأدوات إحصائية وصفية. )SPSS.V 54 ( فردا تم تحليل البيانات باستخدام الحزمة الإحصائية ) 22 ( كشفت نتائج الدراسة أن الفرضية الاولى أنو توجد أثر ذات دلالة إحصائية ضرورة الحاجة لاستخدام معايير التدقيق الجزائرية والاسترشاد بها والفرضية الثانية توجد أثر ذات دلالة إحصائية أثر العمل بمعايير التدقيق الجزائرية في إعداد تقرير الدراجعة الخارجية توجد أثر ذات دلالة إحصائية الصعوبات التي تحول دون تطبيق الددقق الخارجي لدعايير التدقيق الجزائرية وىذا يدل على ان معايير التدقيق الحديثة الجزائرية جاءت لضبط عمل الددققين وتوجيههم للعمل بصورة أكثر مثالية. كلمات الدفتاحية: معايير التدقيق، التدقيق، الدراجعة.""Abstract: This study represents a study of his analysis of modern Algerian auditing standards (an analytical study of accountants and accountants). The literature to clarify the theoretical background of his study of his analysis of the modern Algerian auditing standards (an analytical study of accountants and accountants), and the second method is survey (analytical) through an exploratory study through the questionnaire as a tool for data collection, as the coefficient of honesty was measured as it reached a high degree From the reliability of a sample of (45) individuals, the data were analyzed using the statistical package (SPSS.V22) and descriptive statistical tools. The results of the study revealed that the first hypothesis is that there is a statistically significant effect of the need to use the Algerian auditing standards and be guided by them, and the second hypothesis is that there is a statistically significant effect of the effect of working with the Algerian auditing standards in preparing the external audit report. There is a statistically significant effect of the difficulties that prevent the external auditor from applying the standards Algerian auditing, and this indicates that the Algerian modern auditing standards came to control the work of auditors and direct them to work in a more ideal manner. Keywords: auditing standards, auditing, auditing."
Keywords: معايير التدقيق، التدقيق، الدراجعة; auditing standards, auditing, auditing.